Understanding Student Perceptions of Artificial Intelligence Technology: Case Study of Accounting Education Student, Universitas Muhammadiyah Surakarta - Dian Selasih; Suranto (South Sulawesi Education Development (SSED), 2024)
This research was conducted to understand the views of Accounting Education students at Universitas Muhammadiyah Surakarta regarding the application of Artificial Intelligence (AI) in accounting education. The main problem faced is the lack of understanding of the effective application of AI and its impact on the role of accountants in the future. This research adopts a case study method with a qualitative approach. Data was obtained through in-depth interviews with nine interviewees who are students with accounting education backgrounds. The results show that, although most students are aware of AI technology in accounting, few actually understand how it works. Their perceptions vary, with some seeing AI as a tool that can improve efficiency, while others are concerned about the potential for AI to replace the role of human accountants. These findings point to the need to improve technological literacy among students so that AI can be optimally utilised in accounting.